Anti-inflammatory effects of Aesculus hippocastanum L. tincture and the pro-/antioxidant bodily state of rats with adjuvant arthritis - VASILIAUSKAS, Audrius; LEONAVIČIENĖ, Laima; VAITKIENĖ, Dalia; BRADŪNAITĖ, Rūta; LUKŠIENĖ, Aloyza (Acta medica Lituanica, 2010)
Background. Conventional therapies show only limited effects on rheumatoid arthritis (RA) and are helpful in controlling the symptoms, but in cases of chronic, prolonged RA they are unsatisfactory and associated with various side effects. So, the use of complementary / alternative medicine, predominantly herbal therapies, by sufferers of rheumatic diseases is highly prevalent and increasing. The aim of the study was to evaluate the antiinflammatory effects of Aesculus hippocastanum L. (AH) tincture on the pro-/antioxidant bodily status in rats with adjuvant arthritis (AA).Materials and methods. Fifty Lewis rats of both sexes were used. AA was induced in 40 animals by a single injection of 0.1 ml of complete Freund’s adjuvant into the left hind paw. Body weight and the anti-inflammatory effects of AH, assessed by joint swelling, were determined three times a week in the control and test groups of animals. Daily oral administration of three different doses of AH (2.4, 4.8 and 9.5 mg/kg calculated to the dry weight of the tincture) were performed. At the end of the trial, blood indices, histological changes in the inflamed joints, oxidative products such as malondialdehide (MDA), anti-oxidative enzyme catalase (CAT), superoxide dismutase (SOD) and total antioxidant activity (AOA) in the serum and gastric mucosa tissue homogenates were evaluated.Results. Female rats treated with a middle dose (4.8 mg/kg) of AH tincture showed the lowest joint swelling, which significantly differed from the control AA group at the end of the experiment. The treatment improved the systemic parameters of the disease, such as blood indices and the weight of internal organs, showed no toxicity on the main organs and was selected for investigating the pro-/antioxidant indices of the blood serum and gastric mucosa homogenates. There were significant differences between sexes in terms of the pro-/antioxidant status of the serum. A lower MDA level and statistically significant AOA in female rats with AA were observed. Although the treatment lowered the MDA level and increased CAT activity in animals of both sexes, a significant difference remained between males and females: the latter showed a lower level of MDA and a higher CAT activity. Development of AA significantly increased the MDA level and decreased CAT activity, but only slightly affected SOD and AOA activity in gastric tissue homogenates. Their incubation with AH tincture had a positive effect, especially in female rats in which a significant decrease of MDA and a higher CAT activity were found in arthritic rats and elevated SOD activity in healthy rats. However, the pro-/antioxidant status of gastric tissue homogenates did not significantly differ between male and female rats.Conclusions. The results of the study clearly indicate that AH may be beneficial due to its anti-inflammatory and anti-oxidant effects. The best effect was shown by the middle dose in female rats with AA. The in vivo anti-inflammatory and antioxidant effects of the herbal tincture may be the promising features for its prospective use as supplementary therapy beside the conventional treatment.Keywords: rats, adjuvant arthritis, pro-/antioxidant activity, herbal tincture